1994
DOI: 10.1136/gut.35.11.1551
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic gastrostomy in a general hospital: prospective evaluation of indications, outcome, and randomised comparison of two tube designs.

Abstract: The indications for percutaneous endoscopic gastrostomy (PEG) and patient outcome, were examined prospectively in the setting of a general hospital. In the course of 26 months, 76 patients underwent PEG (median age 62 years (range 18-99)) and were followed up for 6887 patient days. The median (range) duration of PEG feeding was 93 (3-785) days. The procedure was carried out for neurological indications in 76% of cases (stroke 51%) and 53% of patients were severely malnourished (body mass index <17 kg/M2) at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 11 publications
2
19
2
1
Order By: Relevance
“…Risk factors for aspiration include supine position, sedation, neurological impairment and advanced age [16]. Since many patients undergo PEG-tube placement because of stroke or traumatic brain injury, this population with neurological disorders is at an inherently high risk of aspiration [29]. Although a few patients aspirate during PEG-tube placement, the great majority of aspiration events occur at a later time which is unrelated to the PEG procedure [30].…”
Section: Discussionmentioning
confidence: 97%
“…Risk factors for aspiration include supine position, sedation, neurological impairment and advanced age [16]. Since many patients undergo PEG-tube placement because of stroke or traumatic brain injury, this population with neurological disorders is at an inherently high risk of aspiration [29]. Although a few patients aspirate during PEG-tube placement, the great majority of aspiration events occur at a later time which is unrelated to the PEG procedure [30].…”
Section: Discussionmentioning
confidence: 97%
“…[114][115][116][117][118] Gastric tears are a rare occurrence during PEG placement. 108,119 Prevention of such injuries may be best achieved by ensuring adequate transillumination and finger indentation when placing the PEG and by use of the "safe-tract" technique. 120,121 The optimal management of gastric laceration, peritonitis, or colonic perforation is poorly studied, although surgical exploration will likely be required.…”
Section: Adverse Events Of Percutaneous Endoscopic Enteral Accessmentioning
confidence: 99%
“…index [8,14,18,[19][20][21], except for one prospective cohort study in 76 patients that showed nutritional improvement [22]. A comprehensive program of hand feeding is still preferred.…”
Section: Indicationsmentioning
confidence: 99%